2017
DOI: 10.1161/jaha.117.006084
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Hemodynamic Measures of Right Ventricular Diastolic Function: Translating Tissue Biomechanics to Clinical Relevance

Abstract: BackgroundRight ventricular (RV) diastolic function has been associated with outcomes for patients with pulmonary hypertension; however, the relationship between biomechanics and hemodynamics in the right ventricle has not been studied.Methods and ResultsRat models of RV pressure overload were obtained via pulmonary artery banding (PAB; control, n=7; PAB, n=5). At 3 weeks after banding, RV hemodynamics were measured using a conductance catheter. Biaxial mechanical properties of the RV free wall myocardium were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 37 publications
6
54
0
1
Order By: Relevance
“…The qualitative contribution of myofibers and (perymysial) collagen fibers remained unchanged in the PAH tissues such that the behavior of the RVFW was still governed by myofiber response alone in the low strain regime, 33 and collagen fibers and their interaction with myofibers began to gradually contribute to the behavior as their recruitment proceeded (Fig. 6).…”
Section: Resultsmentioning
confidence: 98%
“…The qualitative contribution of myofibers and (perymysial) collagen fibers remained unchanged in the PAH tissues such that the behavior of the RVFW was still governed by myofiber response alone in the low strain regime, 33 and collagen fibers and their interaction with myofibers began to gradually contribute to the behavior as their recruitment proceeded (Fig. 6).…”
Section: Resultsmentioning
confidence: 98%
“…Uniaxial and biaxial mechanical tests are the most common methods to investigate the ventricular mechanical property after tissue harvest (Figure 3). While the uniaxial mechanical test offers a quicker and easier examination of the material mechanical property, the biaxial mechanical test better mimics the in vivo loading conditions and provides more comprehensive measurements of the anisotropic mechanical behavior [17,19,20,22,[39][40][41]. Both methods have been used in prior studies of LV and RV mechanical properties [17,20,[22][23][24][25][26][27][28][29][30][39][40][41][42][43][44][45][46] (please see Table 1 for a summary of these studies).…”
Section: Uniaxial and Biaxial Tensile Mechanical Testsmentioning
confidence: 99%
“…The characterization of the anisotropic behavior of ventricles is highly dependent on the definition of the biaxial coordinate system. To date, there are two main types of coordinate systems: the main fiber and cross-fiber coordinate system [17,30,44], and the outflow tract and cross-outflow tract coordinate system [20,29,40]. Using the former coordinate system, it is consistently observed that the tissue behaves stiffer in the fiber direction compared with the cross-fiber direction [22].…”
Section: Anisotropic Behavior Of Ventriclesmentioning
confidence: 99%
See 2 more Smart Citations